The Russian Siege On Ukraine : An International Law Perspective - Ashray Behura (My University, 2016)
The Russian siege on Ukraine comprised of flagrant violations of International Law, ranging from open and routine incursions, the annexation of Crimea (which was only recognized by one State i.e. Russia) and engaging in an armed conflict. Conspicuous violations included violations of principles enshrined within the U.N. Charter and various multilateral and bilateral treaties. A plethora of options in regards to recourse which can be taken by Ukraine to quell and circumvent Russia's armed intervention are present, however the same only presents itself as a paradox of choice. This is because even though a wide array of remedies are available to Ukraine, it is unlikely that it will materialize considering that Russia is a European powerhouse and due to the stature it commands. The likeliest remedy which can be provided to Ukraine is the provision of reparations by the ICJ in accordance with ARSIWA and other cases decided by this forum court such as the Rainbow Warrior case, Corfu Channel case etc. Greater readiness to counter such blatant violations of fundamental international law principles are necessitated to be adopted by international organizations and other States alike or else this volatility which is seemingly ever-present in Ukraine which has endangered its territorial integrity, state sovereignty and political independence, has threatened to spill in the neighbouring countries, especially considering that no significant legal ramifications have been suffered by the Russian Federation going on to show the irrelevance of International Law.
Keywords: LAW/JURISPRUDENCE::Other law::International law